The Concept оf the Legal Collisions - Priyma, Serhiy; Erofeeva, Maria (Theory and practice of jurisprudence, 2023)
The article considers the conflict of law as one of the drowbacks of the law. It has been established that legal conflicts are an objectively existing, natural defect of law that arises due to various objective and subjective circumstances. To realize the purpose of the article, the following main features of legal conflicts were singled out: 1) their essence is that they are an excess of legal regulation. At the same time, three conditions are necessary for the emergence of a legal conflict: two or more valid legal norms; regulate the same social relationship; such regulation is carried out in different ways. 2) They exist solely between legal norms, as the rules of behavior of the relevant persons; 3) arise at the stage of law-making, but it is revealed at the stage of law application and is resolved with the help of appropriate means. The article singles out the following reasons for the emergence and existence of the legal conflicts: 1) violation of rules and failure the requirements of the law-making technique; 2) insufficient professional qualification of authorized subjects of law creation; 3) unclear demarcation of the law-making competence of authorized subjects; 4) a large number of legal norms, due to which both difficulties in the work of norm design bodies and errors in legal qualification by the law enforcement and law realization bodies are possible; 5) the simultaneous action of the norms of different historical eras - Soviet and Ukrainian - in Ukrainian legislation. The article also considers the areas in which legal conflicts arise and proves that they have the most harmful effect on the realization of the legal certainty principle, because the ambiguity and contradiction of legal norms, which are the violation of this principle and are the basis for the emergence of legal conflicts, and therefore failure the requirements of this principle is one of the methods to reduce the conflict of law. Legal conflicts are defined as a type of legal defect that arises due to the implementation of excessive legal regulation of social life, which leads to a contradiction between the valid legal norms in the regulation of the same social relations.